Bioelectric methods to detect tree damage caused by fire. II. Eucalyptus globulus - Bara, S.; Vega, J. A.; Rozados, Mª. J. (Forest Systems, 1994)
Tree stem electric conductivity, biocurrents and square waves voltage attenuation and change of shape were periodically measured for eighteen months to detect changes originated by an experimental moderately intense fire (480 Kw · m-1) on E. globulus trees. Lethal temperatures at the inner bark of the most part of trees were recorded for several minutes during the fire. Two months after fire epicormic shoots, on more than the half of trees, were observed and one year after fire, leaves decolorization in the half of them was conspicuous. There was no evidence of root damage by the heat pulse. Conductivity significantly decreased for the burnt trees when compared to the control trees along the period of study. Ten days post-fire measurements gave an useful information to estimate the recovery or deterioration trend of individual trees in the next months following the fire. Biocurrents values were sigfnicantly lower for burnt trees than for control, but with a lower signification than conductivity. Square waves transmission (one probe method) showed, in the burnt trees, output voltages significantly higher than in control ones, and also higher V50/V50k ratio. Three probe method also gave output voltages significantly higher in burnt trees than in controls. 50 Hz and 1KHz were the best frecuencies of characterize the damage, and P1 and P3 the best positions of probes.